Helicobacter pylori and histopathological findings in patients with dyspepsia - Cansel TÜRKAY; Mustafa ERBAYRAK; Nükhet BAVBEK; Sibel YENİDÜNYA; Elife ERASLAN; Benan KASAPOĞLU (Turkish Journal of Gastroenterology, 2019)
-